Multiple Cropping for Raising Productivity and Farm Income of Small Farmers - Paudel, Mina Nath (Journal of Nepal Agricultural Research Council, 2016)
Multiple cropping is an agriculture system long adopted by marginalized small holder farmers especially in hills and mountains. This practice was a meant to enhance farm productivity when farming area is limited. Here, in this paper, a brief review on the benefits of multiple cropping is presented focusing on the practices adopted by marginalized farmers, in general. In multiple cropping, it is generally argued that the practice favors an efficient utilization of resources like air, water, light, space, and nutrients by companion crops in both temporal and spatial dimensions due to their differential growth habits and seasonality. Multiple cropping could be one of the viable alternatives to cope uncertainties and changes, where food and nutritional uncertainty looming large. The ultimate outcome of multiple cropping could be visualized in adverse or harsh environment for increase agriculture production, livelihood and income. Various food products are obtained through multiple cropping. Land equivalent ratio (LER), relative yield total (RYT) and income equivalent ratio (IER) can be increased with mixed/intercropping systems. Multiple cropping helps in getting more than one crop simultaneously, so even if the selling price of one commodity is less, the other might compensate. In the tropics, smallholder farms, which produce over 60% of the food resources of developing nations from intercropping of cereals with many crops mostly legumes, had been the field of much investigation because of synergistic effects of diversifying food production and household cash incomes in these systems. This clearly implies the importance of multiple cropping for small farmers who constitute majority in the developing countries.